2023
DOI: 10.21203/rs.3.rs-2728195/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surgical Treatment Effect of Distal Humeral Shaft Fractures: A Prospective Cohort Study on Comparison of Lateral and Posterior Plating techniques

Abstract: Objective: The purposes of this study were to prospectively compare the clinical outcomes of distal humeral shaft fractures treated by lateral plating technique and posterior plating technique. Material and methods: From Jan 2017 to Aug 2019, fifty-one patients with distal humeral shaft fractures treated by lateral or posterior plating technique were collected. Patients were divided into two groups: the lateral plating group (group I, 28 patients) and the posterior plating group (group II, 23 patients). There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The surgeon has rich experience in the application of reconstruction locking plate and PFNA, so the surgical incision, intraoperative blood loss and operation time have no signi cant increase (p>0.05). Zhang Tao et al [21] showed that PFNA has the advantages of short operation time, less intraoperative blood loss, simple operation, safety and reliability, and is an ideal internal xation method for intertrochanteric fractures. However, there is no internal xation device to reconstruct the lateral wall and x intertrochanteric fractures at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon has rich experience in the application of reconstruction locking plate and PFNA, so the surgical incision, intraoperative blood loss and operation time have no signi cant increase (p>0.05). Zhang Tao et al [21] showed that PFNA has the advantages of short operation time, less intraoperative blood loss, simple operation, safety and reliability, and is an ideal internal xation method for intertrochanteric fractures. However, there is no internal xation device to reconstruct the lateral wall and x intertrochanteric fractures at the same time.…”
Section: Discussionmentioning
confidence: 99%